ANALISIS RESIKO USAHATANI UBI KAYU (Manihot Utilissima) DI DESA TANJUNG KEMALA BARAT KECAMATAN MARTAPURA KABUPATEN OKU TIMUR (JASEP, 2021)
Risk Analysis of Rainfall Farming in Tanjung Kemala Barat Village Martapura Sub-district, OKU Timur Regency. This study aims: to calculate income and to analyze income risk in cassava farming in Tanjung Kemala Barat Village Martapura District, OKU Timur Regency. This research was conducted in Tanjung Kemala Barat Village, Martapura Sub-district, OKU Timur District, Research Time Implementation was conducted in November until December 2017. The research method used in this research is survey method. Sampling method used is stratified random sampling method. Of the total population of 69 farmers were taken 30 peasants. The research area is determined based on the largest cassava farming area in East OKU Regency. Characteristics of sample farmers are the land area of ​​1 ha, ¾ ha, ½ ha. Farmers age range from 30 to 59 years old and education level between elementary school graduates up to university. Based on the results of data processing shows that the average number of income farmers who do cassava farming in the Village of West Tanjung Kemala Martapura District of East OKU regency of 10.888.189 / year. And cassava farming produces coefficient of variation / CV 0,019 <0,5 then value L> 0, then the farming will have chance to avoid from loss. Keywords: Analysis, Risk, Cassava